RELATIONSHIP OF SERUM ADIPONECTIN AND RESISTIN LEVELS WITH THE SEVERITY OF LIVER FIBROSIS IN PATIENTS WITH CHRONIC HEPATITIS B - Čustović, Nerma; Rašić, Senija (Journal of Medical Biochemistry, 2021)
Background: Recent research has closely linked adipocytokines to progression of liver inflammation and fibrosis in patients with non-alcoholic liver disease. The aim of this study was to determine the relationship ofserum adiponectin and resistin levels with the severity of liver fibrosis in patients with chronic hepatitis B (CHB), depending on the duration of antiviral therapy.Methods: The cross-sectional studyincluded75 patients with CHB divided into two groups: T1 group(on antiviral therapy for up to 2 years) and T2 group (on antiviral therapy over 2 years). Control group consisted of 40 healthy persons. Serum concentrations of adiponectin and resistin were estimated with ELISA method, while degree of liver fibrosis was determined using FIB-4and APRIscore.Results:The higher values of serum resistin concentration were verified in patients with CHBcompared to healthy controls. The mean level of serum resistin concentration was significantly higher in group of patients with higher FIB-4 score (9.12±3.39 vs. 5.58±3.36 ng/mL, p = 0.001), as well as APRI score (17.45 ± 3.96ng/mL vs.4.82 ± 1.11 ng/mL, p = 0.001). Positive correlation was found between serum resistin levels and degree of liver fibrosis (p < 0.001). There was no significant difference between mean serum adiponectin levels according to the values of FIB-4 and APRI scores.Conclusions:Serum resistin concentration could be a potential noninvasive biomarker of the severity of liver fibrosis in patients with chronic hepatitis B on antiviral therapy.
Keywords: adipocytokines, APRI, FIB-4, hepatitis B